PENGARUH RETURN ON ASSETS, CURRENT RATIO, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM - Trismayarni Elen; Saskia Dwi Nurissa (Unversitas Prof. Dr. Moestopo (Beragama), 2023)
The objective of this study is to determine the effect of return on assets (ROA), current ratio (CR), dan debt on equity ratio (DER) on stock prices. This study uses secondary data from the annual financial reports of food and beverage companies that obtained on Indonesia Stock Exchange (IDX) official website for 2019 - 2021. Sampling technique is purposive sampling method and 24 companies were found that matched the criteria. The result of this study shows that only return on assets (ROA) has a positive effect on stock prices, but current ratio (CR), dan debt on equity ratio (DER) has no positive effect on stock prices.